Legal support for work of small and medium-sized businesses (Journal of actual problems of jurisprudence, 2020)
Analysis of the economic situation in Kazakhstan clearly demonstrates a significant increase in the role of small and medium-sized businesses, which is an important strategic resource that can ensure economic growth, the effectiveness of economic interactions and the enhancement of national welfare. However, small business in the Republic of Kazakhstan has to face serious difficulties arising in the course of a complex set of institutional transformations, among which general economic instability, imperfection of legislation and tax system, financial problems, numerous administrative barriers, lack of necessary knowledge, skills and experience. The aim of the research is to substantiate theoretical and practical provisions aimed at improving the legal regulation of the activities of small and medium-sized businesses. The methods of the research: system method, logical method, analysis, synthesis, formal legal method, method of comparative law, method of technical and legal analysis, as well as methods of other sciences – historical, statistical, linguistic. Key words: small and medium-sized businesses, economic activity, the legal regulation, the credit and financial system.